Pengaruh Substitusi Tanah Putih pada Mortar Geopolimer Berbahan Dasar Fly Ash dengan Aktifator Natrium Hidroksida - Priastiwi, Yulita Arni; Hidayat, Arif; Daryanto, Dwi; Badru, Zidny Salamsyah (MEDIA KOMUNIKASI TEKNIK SIPIL, 2020)
The presence of white soil in a geopolymer mortar affects the physical and mechanical properties of the mortar itself, especially in compressive strength, density and modulus of elasticity produced. Geopolymer mortar composed of fly ash, sand, water, and NaOH which acts as an alkaline activator compared to mortar from the same material, but white soil from Kupang is added as a substitution of fly ash. Specimens are made in six variations. Geopolymer mortar composers using a ratio of 1 binder: 3 sand with w/b of 0.5. Binder composed of fly ash with white soil substitution of 0; 5; 10; 15; 20 and 30% by weight of fly ash. An activator NaOH 8M solution was added to the mixture. Both white soil and fly ash pass of sieve no. 200 with a moisture content of 0%. Mortar made measuring 5x5x5 cm. The mortar was treated by the oven of method at 60 oC for 24 hours until the mortar does not change in weight. The test results show geopolymer mortar with 15% substitution of white soil to fly ash has the highest compressive strength, density and modulus of elasticity among other variations. In all mortar variations, compressive strength at 14 days has reached 75% of strength at 28 days.